Abschlussarbeiten an Nordrhein-Westfälischen Designschulen 1988. (Hagen : Karl Ernst Osthaus Museum, 1988)
Herzog, Petra ; Kappesser, Christoph ; Sous, Vera ; Hunkler, Urs ; Meier, Norbert ; Oberück, Hermine ; Pfaffenbach, Katja ; Stillert, Gerda ; Wille, Judith ; Yalcin, Aydin ; Dietrich, Jens ; Hassinger, Sybille ; Pietsch, Angelika ; Singer, Tina ; Waldschmidt, Rainer ; Hagen, Dagmar ; etc.
Abschlussarbeiten an Nordrhein-Westfälischen Designschulen 1988, Karl Ernst Osthaus Museum, Hagen, 19.11. - 04.12.1988
boek